Advanced Programming in the UNIX® Environment : Second Edition - Rago, Stephen; Stevens, W. (Addison-Wesley Professional, 2005)
"Stephen Rago's update is a long overdue benefit to the community of professionals using the versatile family of UNIX and UNIX-like operating environments. It removes obsolescence and includes newer developments. It also thoroughly updates the context of all topics, examples, and applications to recent releases of popular implementations of UNIX and UNIX-like environments. And yet, it does all this while retaining the style and taste of the original classic." --Mukesh Kacker, cofounder and former CTO of Pronto Networks, Inc. "One of the essential classics of UNIX programming." --Eric S. Raymond, author of The Art of UNIX Programming "This is the definitive reference book for any serious or professional UNIX systems programmer. Rago has updated and extended the classic Stevens text while keeping true to the original. The APIs are illuminated by clear examples of their use. He also mentions many of the pitfalls to look out for when programming across different UNIX system implementations and points out how to avoid these pitfalls using relevant standards such as POSIX 1003.1, 2004 edition and the Single UNIX Specification, Version 3." --Andrew Josey, Director, Certification, The Open Group, and Chair of the POSIX 1003.1 Working Group " Advanced Programming in the UNIX® Environment, Second Edition, is an essential reference for anyone writing programs for a UNIX system. It's the first book I turn to when I want to understand or re-learn any of the various system interfaces. Stephen Rago has successfully revised this book to incorporate newer operating systems such as GNU/Linux and Apple's OS X while keeping true to the first edition in terms of both readability and usefulness. It will always have a place right next to my computer." --Dr. Benjamin Kuperman, Swarthmore College Praise for the First Edition " Advanced Programming in the UNIX® Environment is a must-have for any serious C programmer who works under UNIX. Its depth, thoroughness, and clarity of explana-tion are unmatched." -- UniForum Monthly "Numerous readers recommended Advanced Programming in the UNIX® Environment by W. Richard Stevens (Addison-Wesley), and I'm glad they did; I hadn't even heard of this book, and it's been out since 1992. I just got my hands on a copy, and the first few chapters have been fascinating." -- Open Systems Today "A much more readable and detailed treatment of UNIX internals can be found in Advanced Programming in the UNIX® Environment by W. Richard Steven...